Renal Resistive Index in Early Detection of AKI after Neurosurgery: A Case Series - Sethiono, Aldy; Parami, Pontisomaya; Wirgunatha, I Made Wirga (Jurnal Anestesiologi dan Terapi Intensif, 2025)
Postoperative acute kidney injury (AKI) is a frequent yet underrecognized complication in neurosurgical patients, often contributing to increased morbidity and mortality. Brain injury can trigger systemic effects, including sympathetic overactivation, inflammatory responses, and hemodynamic instability, all of which predispose patients to renal dysfunction. The Renal Resistive Index (RRI), obtained by Doppler ultrasonography, reflects intrarenal vascular resistance and has emerged as a promising early marker of AKI. This case series describes three patients undergoing decompressive craniectomy for intracranial hemorrhage who had normal preoperative renal function and subsequently developed stage 1 AKI according to Kidney Disease; Improving Global Outcome (KDIGO) guideline within 24 hours postoperatively. In each case, an elevated RRI (>0.7) measured during the early postoperative period preceded the rise in serum creatinine and the reduction in urine output. The consistent pattern across these patients highlights the potential utility of RRI as a noninvasive, bedside predictor of postoperative AKI in neurosurgical populations. The findings support the clinical relevance of integrating RRI into perioperative monitoring, particularly in high-risk patients where early detection of renal dysfunction may guide timely interventions to optimize hemodynamic stability and prevent further injury. Further prospective studies with larger cohorts are warranted to validate these observations and establish standardized thresholds for practice.